Molecular identification of Araecerus fasciculatus and its endosymbiotic bacteria - B.G. Sangeetha; S. Lekshmi; Gadha Dileep; P. Drishya; E.R. Harish (JOURNAL OF ROOT CROPS, 2024)
Araecerus fasciculatus are one of the important storage pests of cassava, associated with a wide variety of bacterial endosymbionts that confer many ecologically relevant traits to the host insect. Endosymbiotic bacteria (ESB) play a vital role even in the physiology of the host, hence identification of ESB associated with the storage pests will help to develop important strategies for the management of the noxious pest. In the present study molecular characterization of the Araecerus fasciculatus and endosymbiotic bacteria associated with them, was done. By molecular characterization they were identified as Araecerus fasciculatus and sequences were deposited at NCBI with accession no OR415335. Further, the genomic DNA was isolated from each of the EPB isolates and PCR amplification of 16S rRNA gene was carried out using universal primers. The 16S rDNA gene sequences of endosymbiotic bacterial isolates were generated by sequencing the PCR product and were aligned with each other by using BioEDIT software. The nucleotide sequences were compared with those in the NCBI databases using the Basic Local Alignment Search and were identified as were confirmed as Bacillus megaterium. The taxonomy had been recently changed and was renamed Priestia megaterium, which is a new separate genus from Bacillus. The 16S rRNA gene sequences were also deposited at NCBI database with accession no OR418413. From the aligned sequences phylogenetic tree was constructed by the Neighbor-Joining method using MEGA version 11.